Severe apparently isolated fetal ventriculomegaly and neurodevelopmental outcome. (19th July 2017) - Letouzey, Mathilde; Chadie, Alexandra; Brasseur‐Daudruy, Marie; Proust, François; Verspyck, Eric; Boileau, Pascal; Marret, Stéphane
Abstract: Objective: Our aim is to assess the neurodevelopmental outcome of children with a prenatal diagnosis of apparently isolated severe ventriculomegaly (SVM). Method: This is a retrospective cohort study from 1994 to 2011. We included fetuses with unilateral or bilateral ventriculomegaly equal to or greater than 15 mm at prenatal ultrasound and confirmed by magnetic resonance imaging, whose parents chose continuation of pregnancy past 22 weeks, and with no associated findings at diagnosis (i.e. no brain malformation or cerebral lesions, normal karyotype, no other congenital abnormalities by ultrasound, and negative toxoplasma, rubella, cytomegalovirus, and herpes test. Children were followed up for at least 2 years. Children were classified into three groups: normal, moderate, or severe abnormalities according to psychomotor developmental stages and/or a visual or hearing impairment and/or behavioral disorders. Results: Twenty‐one patients fulfilled the study criteria. SVM was diagnosed at an average gestational age of 30 weeks (range 22–37 weeks). Head circumference was >95th centile in 39% of them. The etiology of SVM was intraventricular hemorrhage in 6 (29%), stenosis of the aqueduct of Sylvius in 3 (14%), and undetermined in 12 (57%). Neurosurgery was performed in four infants, and ventriculoperitoneal shunts were inserted in three. At a mean age at last follow‐up of 8.4 years, neurodevelopmental outcome was normal in 62% and moderate and severely impaired in 14% and 24% of children, respectively. There was no association between neurologic outcome and severity of ventricular dilation at prenatal imaging, gestational age at initial diagnosis of SVM, or etiology of the ventricular dilatation. Conclusion: The majority of children with apparently isolated SVM show normal neurodevelopmental outcome. No prenatal risk factor identify cases at higher risk for severely abnormal neurologic outcome. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? VM is one of the most frequent brain abnormalities encountered during prenatal obstetric ultrasound screening. There is scarce data on the outcome of infants with prenatally diagnosed isolated severe VM. What does this study add? At a mean age of 8.4 years, neurodevelopmental outcome was normal for 62% of children with apparently isolated severe VM prenatally diagnosed. Moderate and severe impairment were identified in 14% and 24% of children. No prenatal risk factor was identified with prognostic ability for neurologic outcome.